ON FUZZY ANS – IDEAL OF B – ALGEBRA - SALEH ABED, ALAA (Al-Qadisiyah Journal of Pure Science, 2019)
The purpose of this investigation is to characterize the ideal of fuzzy ANS – ideal of B – algebra and the relationship between it and the fuzzy – translation , fuzzy – multiplication, fuzzy extension and fuzzy magnified. Then we attach it by some theorems .